'Why didn't you tell me that before?' Engaging undergraduate students in feedback and feedforward within UK higher education. Issue 3 (16th March 2021) - Wolstencroft, Peter; de Main, Leanne
ABSTRACT: This paper explores the use of audio feedback with 182 final year undergraduate students in a post-92 university studying on a Business Management undergraduate degree. It looks at the problems associated with traditional forms of feedback and feedforward and explores the reasons why students fail to engage with the comments made by lecturers regarding their performance in assessment. Feedback and feedforward are widely recognised to be vitally important for students looking to improve their grades, but the authors found that only 60% accessed their feedback when it was given in the standard, written, form with reasons ranging from students having an instrumental approach to assessment, through to a perception that the comments made were generic and lacking in meaning. This research has demonstrated that an alternative approach to feedback and feedforward, using audio rather than written communication, can increase both the number of students accessing feedback, but also students' engagement with what has been said. By using an audio-based method to hear both the comments and the final grade, students felt more thought had been put into the marking process and that comments were personalised to them, making them more likely to engage with it.